194 Quantifying and addressing the shortage of swimming teachers in Victoria, Australia. (20th November 2022) - Calverley, Hannah; Matthews, Bernadette; Tesone, Liz
Abstract : Background: Speculation of a swim teacher shortage in Victoria following the 2020/21 COVID-19 pandemic was based on anecdotal evidence. Addressing this issue was vital due to the importance of swim teachers in reducing drowning risk, and little published evidence exploring recruitment and retention of swim teachers. Methods: Methods included: review of peer-reviewed and grey literature to identify recruitment and retention strategies; surveys of Victorian swimming lesson providers, requesting current and retrospective data on swimming lesson provision, waiting lists, and staff; and follow-up emails to survey participants to gain further industry insights about strategies to assist the aquatic industry in ensuring sufficient staffing to meet demand post COVID-19. Results: Thirty-nine organisations completed the survey; approximately 25.6% of the Victorian swim teaching market share. Number of employed swim teachers was significantly lower in 2021 compared to 2019 (p = 0.003) and 2020 (p = 0.011); an additional 1, 833 swim teachers are required in Victoria to meet demand. Eight practical recommendations to address the shortage are provided, incorporating: obtaining and maintaining qualifications; retention strategies; recruitment; and employment pathways. Conclusions: The provision of Victorian swim teachers does not meet current demand. Urgent action is required to recruit and retain more permanent staff, using strategies which incentivise the swim teaching role for staff and facilities, and offer role progression. Learning Outcomes: This is a call-to-action for a contribution of time and resources to address the Victorian swim teacher shortage. Without such action, the water safety skills and knowledge of Victorians will likely be impacted.